Vitamin D supplementation prior to or during COVID-19 associated with better 3-month survival in geriatric patients: Extension phase of the GERIA-COVID study. Issue 213 (October 2021) - Annweiler, Cédric; Beaudenon, Mélinda; Simon, Romain; Guenet, Mialy; Otekpo, Marie; Célarier, Thomas; Gautier, Jennifer; ,
Abstract: Background: The objective of this extension phase of the quasi-experimental GERIA−COVID study was to determine whether vitamin D3 supplementation taken prior to or during COVID-19 was associated with better 3-month survival in geriatric patients hospitalized for COVID-19. Methods: Intervention group was defined as all participants supplemented with vitamin D3 prior to or during COVID-19 (n = 67). Supplements were either bolus vitamin D3 (ie, 50, 000 IU per month, or 80, 000 IU or 100, 000 IU or 200, 000 IU every 2–3 months), or daily supplementation with 800 IU. Comparator group involved those without vitamin D supplements (n = 28). Outcome was 3-month mortality. Covariables were age, sex, functional abilities, history of malignancies, cardiomyopathy, undernutrition, number of acute health issues, antibiotics use, systemic corticosteroids use, and 25(OH)D concentration. Results: 76.1 % (n = 51) of participants survived at 3 months in Intervention group, compared to only 53.6 % (n = 15) in Comparator group (P = 0.03). The fully-adjusted hazard ratio for 3-month mortality was HR = 0.23 [95 %CI: 0.09;0.58](P = 0.002) in Intervention group compared to Comparator group. Intervention group had also longer survival time (log-rank P = 0.008). Conclusions: Vitamin D3 supplementation was associated with better 3-month survival in older COVID-19 patients.